Baicalein enhances the osteogenic differentiation of human periodontal ligament cells by activating the Wnt/β-catenin signaling pathway. (June 2017) - Chen, Li-Jiao; Hu, Bi-Bo; Shi, Xin-Lian; Ren, Man-Man; Yu, Wen-Bin; Cen, Sheng-Dan; Hu, Rong-Dang; Deng, Hui
Highlights: Baicalein enhanced the osteogenic differentiation of hPDLCs. The optimal dosage of baicalein was 10 μM. DKK-1 significantly reversed the effects of baicalein on hPDLCs. The effects are exerted by activating the Wnt/β-catenin signaling pathway. Abstract: Objective: Periodontium regeneration is one of the most important processes for periodontitis therapy. Human periodontal ligament cells (hPDLCs) play a vital role in the repair and regeneration of periodontal tissues. Our study aimed to investigated the mechanisms underlying the promotion of hPLDCs osteogenic differentiation by baicalein. Design: hPDLCs were obtained from periodontal ligament (PDL) tissues by primary culture. The MTT assay was used to determine the growth curves of hPDLCs treated with different concentrations of baicalein (1.25, 2.5, 5, or 10 μM). Alkaline phosphatase (ALP) staining and Alizarin red S staining were performed to assess osteogenic differentiation of hPDLCs administered baicalein. Osteogenic differentiation-related gene and protein expression levels and Wnt/β-catenin pathway signal changes were assessed by qRT-PCR and Western blotting analysis. Results: The results showed that baicalein decreased the growth of hPDLCs slightly and increased ALP activity and calcium deposition in a dose-dependent manner. The expression of runt-related transcription factor 2 (RUNX2), bone morphogenetic protein 2 (BMP2), Osterix (OSX) and osteocalcin (OCN) were elevated after baicalein administration. Moreover, baicalein strongly activated the Wnt/β-catenin pathway and up-regulated the expression of β-catenin, lymphoid enhancer factor 1 (LEF1) and Cyclin D1. Dickkopf-related protein 1 (DKK-1) significantly reversed the effects of baicalein on hPDLCs. Conclusions: Our findings indicated that baicalein enhanced the osteogenic differentiation of hPDLCs via the activation of the Wnt/β-catenin signaling pathway, which may represent a potential candidate for periodontitis therapy.